Time-temperature approach to assess of the longevity of critical structural elements - Приходько, Р. П. (Scientific Progress & Innovations, 2016)
An analysis of results of the extrapolation of stress rupture curves is performed using the modified base diagram method. The efficiency of the offered algorithms for predicting the creep rupture longevity with the prediction order equal to two or more on the logarithmic time scale is shown. The application areas of the known parametric methods for predicting the stress-rupture strength of materials are specified based on the experimental investigations. It is shown that these methods allow extrapolating the time destruction to the values that exceed the available experimental data by no more than a factor of 10 times with accuracy sufficient for engineering purposes. To extend the prediction capabilities to 300 thousand hours or more on the basis of the test results of limited duration, a modified base diagram method is offered. A linear dependence is offered to approximate the residual function in terms of the base diagram method. In the case where it is impossible to reduce the stress-rupture curves to a common curve, the residual function parameters are determined from the experimental data for one isotherm. In this case, its parameters are the functions of temperature. The advantages of this approach according to Larson-Miller, Orr-Sherby-Dorn, Manson-Succop, Trunin and other parameters are shown during the extrapolation of stress-rupture strength to big longevity.